Discussion of the evidence and conclusions (Scottish Historical and Archaeological Internet Reports, 2005)
Analysis of the location and distribution of the finds across the site and of the individual artefacts have produced little information on the function and chronology of the house as most derive from abandonment and modern levels. The evidence from artefacts is indicative of grain cultivation with ploughing or digging taking place in the vicinity of the house, along with leather processing or the manufacture of wooden or bone artefacts. Analogy with other sites, the association of the steatite vessel and lamp places the building in the Bronze Age.